2009
DOI: 10.1177/0885728809346959
|View full text |Cite
|
Sign up to set email alerts
|

Can Community-Based High School Transition Programs Improve the Cost-Efficiency of Supported Employment?

Abstract: This study investigates the potential impact that community-based, high school transition programs have on the costefficiency of individuals with disabilities when they become adults. Outcomes achieved by 246 supported employees were compared. Results indicated that supported employees who participated in community-based transition programs in high school were more cost-efficient from the taxpayers' perspective than were individuals who received only in-school transition services or received no transition serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Research has shown that many people with an intellectual disability learn work skills better in real job environments, with support to guide their learning, rather than in special or simulated environments (Carter, 2005; Cimera, 2009; Phelps & Hanley‐Maxwell, 1997). Supporting young people with an intellectual disability and/or autism to have employment experiences similar to their neurotypical peers is also essential for developing independence and informed choice around work (Kaehne & Beyer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that many people with an intellectual disability learn work skills better in real job environments, with support to guide their learning, rather than in special or simulated environments (Carter, 2005; Cimera, 2009; Phelps & Hanley‐Maxwell, 1997). Supporting young people with an intellectual disability and/or autism to have employment experiences similar to their neurotypical peers is also essential for developing independence and informed choice around work (Kaehne & Beyer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zihin yetersizliği olan bireylerin iş yaşamına geçiş süreci ile ilgili literatür incelendiğinde zihin yetersizliği olan bireylerin iş yaşamına geçişini planlamaya yönelik bilgilendirici çalışmalara (Cummings, Maddux ve Casey, 2000;Dunn, 1996;Halpern, 1994;King, Baldwin, Currie ve Evans, 2006;Kohler ve Field, 2003;Mazzotti ve diğerleri 2009;Mellard ve Lancaster, 2003), geçişle ilgili görüşlerin belirlenmesine yönelik çalışmalara (Cobb ve Alwell, 2009;Davies ve Beamish, 2009;Ferguson, Ferguson ve Jones, 1988;Foley, Dyke, Girdler, Bourke ve Leonard, 2012;Hendricks ve Wehman, 2009;Landmark, Ju ve Zhang, 2010;Phelps ve Hanley-Maxwell, 1997;Stewart, Law, Rosenbaum ve Willms, 2002;Test ve diğerleri 2009; Wehman ve diğerleri 2014) ve uzun süre devam eden uygulama sonuçlarının değerlendirildiği niceliksel çalışmalara (Baer, Daviso, Flexer, McMahan Queen ve Meindl, 2011;Baer ve diğerleri 2003;Bang ve Lamb, 1997;Blackorby ve Wagner, 1996;Carter, Austin ve Trainor, 2012;Carter, Trainor, Cakiroglu, Swedeen ve Owens, 2010;Carter, Trainor, Ditchman, Swedeen ve Owens, 2011;Cawthon, Wendel, Bond ve Garberoglio, 2016;Cihak, Kessler ve Alberto, 2008;Cimera, Burgess ve Bedesem, 2014;Cimera, Burgess ve Wiley, 2013;Evert-Cimera, 2010;Harvey, 2002;Lehmann, Bassett, Sands, Spencer ve Gliner, 1999;Wagner, 1992;Wagner, Newman, Cameto, Javitz ve Valdes, 2012) rastlanmaktadır. Ülkemizde ise zihin yetersizliği olan bireylerin işe yerleştirilmelerine ilişkin okul yöneticisi ve öğretmenlerin görüşlerinin incelendiği (Gündoğdu, 2010) ve gelişimsel geriliği olan bireylerin iş yaşamına geçiş sürecinin incelendiği (Gürsel, Ergenekon ve Batu, 2007) çalışmalara rastlanmaktadır.…”
Section: Introductionunclassified
“…A possible explanation is that the SE programs focused on staying at jobs when the youth may 'prefer to change jobs as a means of career exploration and identity development' (p. 176). Another study (Cimera, 2010b) among young adults in the US compared outcomes across groups of individuals receiving no transition services, receiving transition services in school or receiving community-based transition services when they were in high school. It was found that only individuals who received services in the community were employed significantly longer than their peers with no transition services.…”
Section: Introductionmentioning
confidence: 99%